Hubungan Operasionalisasi Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4K) Dengan Kesiapan Menghadapi Komplikasi Persalinan Pada Ibu Hamil Trimester III - Ni Kadek Yuniasih; Made Widhi Gunapria Darmapatni; Ni Nyoman Budiani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
Complications of maternal deaths occur during childbirth and delay in community level that was too late to recognize the signs of danger, late decisions and late get handling at the place of reference. These conditions make pregnant women need the right prevention efforts to be ready to face complications of childbirth. The purpose of this study is to know the relation of operationalization of birth planning and complication prevention programwith the readiness to face complications of Labor in third trimester pregnant women at the Public Health Center of Denpasar in 2018. This study type is correlational analysis using croos sectional design. The sample counted 56 samples by using quota sampling method. Data analysis technique to test hypothesis is chi square. The results showed that most (66,1%) of respondents operated of birth planning and complication prevention programcompletely and 64,3% of respondents were prepared to face birth complications. There was a significant correlation between operationalization of birth planning and complication prevention program with pregnant woman readiness to face complication of labor with p value = 0,013. Suggested health officers continue to improve information and education communications to pregnant women and conduct extension activities and health promotion to the community.Keywords: Birthing Planning, Labor Complications